Occurrence and associated factors of self-reported medical errors among Chinese physicians and nurses: a cross-sectional survey - Zejun Li; Liyan Liu; Xiaoyu Zhang; Kewen Yan; Xin Wang; Min Wu; Huixue Xu; Yueheng Liu; Qianjin Wang; Manyun Li; Yuzhu Hao; Li He; et al. (Annals of Medicine)
Background Medical errors (MEs) significantly threaten patient safety globally. This study aimed to explore multidimensional factors associated with self-reported MEs among Chinese physicians and nurses.Methods A cross-sectional online survey using snowball sampling collected 7197 valid responses from Chinese physicians and nurses between October 2020 and April 2022. A self-reported question assessed MEs within the past three months. Sociodemographic characteristics, work-related factors, and mental distress were collected. Data were analyzed using stepwise logistic regression.Results 1285 (17.9%) physicians and nurses self-reported MEs during the previous 3 months. Factors associated with higher odds of self-reported MEs included male sex (OR: 1.44, 95% CI: 1.23-1.69), physician status (OR: 1.48, 95% CI: 1.26-1.73), history of mental illness (OR: 1.49, 95% CI: 1.16-1.91), longer weekly working hours (OR: 1.20-1.23, 95% CI: 1.03-1.47), workplace violence experience (OR: 1.54-1.75, 95% CI: 1.30-2.17), and dissatisfaction with the medical practice environment (OR: 1.20, 95% CI: 1.05-1.37). Conversely, being married (OR: 0.74, 95% CI: 0.62-0.89), holding a bachelor’s degree or higher (OR: 0.82, 95% CI: 0.70-0.97), and having more years of professional practice (OR: 0.96, 95% CI: 0.95-0.97) were associated with lower odds of self-reported MEs. Self-reported MEs were significantly and positively correlated with burnout (OR: 1.40, 95% CI: 1.20-1.62), depressive symptoms (OR: 1.38-1.45, 95% CI: 1.04-1.84), perceived stress (OR: 1.28-1.62, 95% CI: 1.06-2.02), and excessive daytime sleepiness (OR: 1.27-1.46, 95% CI: 1.10-1.79).Conclusions Self-reported MEs are relatively common among Chinese physicians and nurses, and are associated with various factors. Poor workplace conditions and mental distress are linked to an increased risk of MEs. Implementing effective interventions to improve workplace conditions and mental health is crucial for reducing MEs.